Taxonomical, ecological and zoogeographical studies on anisitsiellid water mites (Acari: Hydrachnidia: Anisitsiellidae Koenike, 1910) from Madagascar - Goldschmidt, Tom (Zootaxa, 2008)
Herein the Malagasy Anisitsiellidae are studied for the first time, resulting in records of 24 species in six genera, of which 23 are new to science. Two genera new to science are described: Sotropalpus gen. nov. with the only species S. manga sp. nov., and Bitabulata gen. nov., with B. kelycoxae sp. nov., B. paoma sp. nov. and B. sagai sp. nov. Two new subgenera, Telotaolana subgen. nov. and Cookonia subgen. nov., and nine new species of Nilotonia Thor, 1905 are described: Nilotonia (Dartiella) ivelany sp. nov., N. (Dartiella) onilahy sp. nov., N. (Dartonia) nifymanana sp. nov., N. (Telotaolana) ankaratra subgen. et sp. nov., N. (Telotaolana) hodivaventy subgen. et sp. nov., N. (Telotaolana) kiraro subgen. et sp. nov., N. (Telotaolana) longipalpis subgen. et sp. nov., N. (Cookonia) anjozorobe subgen. et sp. nov. and N. (Cookonia) avomonina subgen. et sp. nov. Two further species (possibly Nilotonia) were found as deutonymphs only and are therefore described tentatively. Mamersella thienemanni K. Viets, 1929, widely distributed in Southern Asia, was found in Madagascar for the first time; the variability of this species is discussed and the deutonymph described. Eight new species of Platymamersopsis K. Viets, 1914 were found, of which two represent a new subgenus — Platymamersopsis (Lavorona) subgen. nov.: Platymamersopsis (s. str.) angulatus sp. nov., P. loharano sp. nov., P. davecooki sp. nov., P. palustris sp. nov. and P. spinalis sp. nov., Platymamersopsis (Lavorona) pinocchio subgen. et sp. nov. and P. (Lavorona) volovitsy subgen. et sp. nov. Additional descriptions are given of Mamersella tototaensis Cook, 1966, Platymamersopsis agnewi K.O. Viets, 1981, P. chutteri K.O. Viets, 1981, P. nordenskioeldi K. Viets, 1914, P. similis Cook, 1966 and P. vietsi Cook, 1966. The morphological patterns, biogeography, diversity and ecology of the Malagasy Anisitsiellidae — especially the krenobiosis of many species — are discussed.